(untitled) (Indian Journal of Public Health Research & Development, 2021)
Aim: Assess the fracture strength of endodntically treated teeth with minimally invasive access cavity design versus conventional one. Methods: Forty four extracted molars were assigned to 4 groups. Conservative Access Cavity, Ninja Access Cavity, Truss Access Cavity, Traditional Access Cavity (n = 11/group/type). Teeth in the Traditional group were prepared following the principles of traditional endodontic cavities. Conservative access prepared by using 2 periapical radiographs to determine canals location. Ninja access scans were plotted on cone beam computed tomographic images for localization of root canal orifices and Truss group were scanned, and merged with cone beam computed tomography, for fabrication of an endodontic guide.The 44 specimens were loaded to fracture in a universal material testing machine. The maximum load at which the teeth fractured and fracture pattern (restorable or unrestorable) were recorded. Results: Regarding the fracture strength, results showed that there was a significant difference between Ninja, Conservative,Truss and traditional access groups with (p < 0.001) and no significant difference between Conservative and Truss groups. Regarding restorability, there was no statistical difference observed between the four groups with (p < 0.001). Conclusion: Teeth with traditional access showed lower fracture strength than the ones prepared with Conservative, Ninja and Truss.